Short Communication. Factors influencing in vitro seeds germination and correlation of antioxidant activity with tissue development in Cedrus deodara - Ahmad, N.; Fazal, H.; Haider Abbasi, B.; Ali, M. (Forest Systems, 2013)
Aim of study: The main objective of this study is to introduce a reliable system for in vitro seed germination. Because Cedrus deodara stands are gradually decreasing in different regions of the world due to overexploitation, natural disasters and lower seed viability. Area of study: Swat is situated at the northwestern corner of Pakistan; with total area of 5337 square km. Total cultivated land is 95281 hectares in 2007, while the area under forest cover is 135427 hectares. Material and Methods: We used MS-medium with or without PGRs for overall in vitro seed germination. To enhance germination frequency, we applied different photoperiods (16hrs-Dark/8hrs-Light and 16hrs-Light/8hrs-Dark) and sterilization reagents (mercuric chloride and ethanol). Synthetic free radical of DPPH (1, 1-diphenyl-2-picrylhydrazyl) was applied for the determination of antioxidant activity Main results: Maximum shoots length (3.6 cm) and root length (2.6 cm) were recorded on MS-medium augmented with BA (1.0 mg L-1) and (GA3) 0.5 mg L-1) under light incubation (16hrs-Light/8hrs-Dark) after 2-3 weeks of inoculation. Without PGRs, maximum root length (4.0 cm, with shoots of 3.2 cm) was observed in dark incubation (16hrs-Dark/8hrs-Light), whereas light incubation produced maximum shoot length (3.5 cm) and minimum root length (1.5 cm). Lower concentration of HgCl2 (0.1%) showed a lower inhibitory effect on shoot and root length (2.4 cm and 2.5 cm) as compared to higher concentrations. The antioxidant potential was also investigated in different Cedrus organs and tissues. Research highlights: These results suggested that this simple protocol is useful for Cedrus deodara conservation and plantlets production for commercial purposes. Key Words: Cedrus deodara; Seed germination; Callus; 6-Benzyladenine; Antioxidant.